Discurso relatado na língua portuguesa em uso: um estudo funcionalista da relação interoracional de projeção porencaixamento - Maria Evane Betonico (2011)
This study investigates the structure of the reported speech that occurs in theses and dissertations in the Portuguese Language in use, more specifically the articulation of clauses that make up the reported speech. It is based on Systemic-Functional Linguistics approach and it takes into account the communicative-interactional function of language because it is intended to have an explanation for the communicative role that the reported speech takes in its configurational semantic profile and the discursive functional role of the formal organization which constitutes it. Based on the hypothesis that the linguistic strategy used in the creation of reported speech is the evidence of involvement of the author with the reader, with himself, with the subject and the socio-cultural context, the aim here is to demonstrate the interrelationship in the clauses in the reported speech. So, it sets up the structure of complex clauses which are reported speech with the interest of explaining the relationship thatmark their ways of use. It examines the occurrences of dicendi verbs compatible with clauses in character of projection as a verbal or mental process and verifies syntactic integration among the clauses of reported speech, from the presence or absence of connectives. Thus it analyses reported speech as a mechanism chosen by the author in the production of linguistic actions.